2012
DOI: 10.1088/0004-637x/763/1/29
|View full text |Cite
|
Sign up to set email alerts
|

Radio and Gamma-Ray Pulsed Emission From Millisecond Pulsars

Abstract: Pulsed γ -ray emission from millisecond pulsars (MSPs) has been detected by the sensitive Fermi space telescope, which sheds light on studies of the emission region and its mechanism. In particular, the specific patterns of radio and γ -ray emission from PSR J0101-6422 challenge the popular pulsar models, e.g., outer gap and two-pole caustic models. Using the three-dimensional annular gap model, we have jointly simulated radio and γ -ray light curves for three representative MSPs (PSR J0034-0534, PSR J0101-642… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Our OG fit finds a significantly larger α and slightly lower ζ . Du et al (2013) modeled the gamma-ray and radio light curves of PSRs J0034−0534, J0101−6422, and J0437−4715 using an annular gap model. Their fits were done by eye but guided by the assumption that the inclination angles should be small (consistent with the possible trend of decreasing α with age for non-recycled pulsars, e.g., Young et al 2010) and by geometric estimates from other wavelengths when possible.…”
Section: Resultsmentioning
confidence: 99%
“…Our OG fit finds a significantly larger α and slightly lower ζ . Du et al (2013) modeled the gamma-ray and radio light curves of PSRs J0034−0534, J0101−6422, and J0437−4715 using an annular gap model. Their fits were done by eye but guided by the assumption that the inclination angles should be small (consistent with the possible trend of decreasing α with age for non-recycled pulsars, e.g., Young et al 2010) and by geometric estimates from other wavelengths when possible.…”
Section: Resultsmentioning
confidence: 99%
“…They found that modulation of the emissivity by E can have a greater effect on the γ -ray light curves than magnetic field geometry alone. Additional light curve modelling for particular pulsars were carried out for OG models of the Crab (Takata, Chang & Cheng 2007;Hirotani 2008) using VRD field structure and for annular gap models for Vela (Du et al 2011), the Crab (Du, Qiao & Wang 2012) and several MSPs (Du, Qiao & Chen 2013) using static dipole field structure.…”
Section: Geometric Light Curve Modelsmentioning
confidence: 99%
“…In order to constrain the emission geometry and locations, they used prior geometric LC fitting invoking the AG to model the peaks, and the CG to model the bridge emission. Du et al (2013) modelled the radio and γ-ray LCs of three MSPs (PSR J0034-0534, PSR J0101-6422, and PSR J0437-4715) using a single-pole AG plus CG model. The challenging three-peaked γ-ray LC of PSR J0101-6422 could be fit invoking emission from both the AG and two zones in the CG, coming from different emission altitudes.…”
Section: Tpc / Og Models In An Ff Magnetospherementioning
confidence: 99%